Prospecção de produtos inovadores com a utilização do bagaço de malte na fabricação de gelatos - Nascimento, Clodoaldo Silva do (2020)
Beer is one of the most consumed drinks in the world, and Brazil is among the largest beer producers, behind only the United States and China. As in most industrial processes, beer production has unit ary operations that generate by-products, such as malt bagasse that is obtained in the filtration of the must. Malt bagasse is considered a secondary product of low value because it is not very useful in the brewing industries, being sold for on average R$ 70.00 a tonne; however this residue has been attracting the attention of many researchers in recent times, due to its composition rich in fibers, proteins, amino acids and various minerals beneficial to human health. Malt bagasse maintains virtually all barley properties even after processes designed for it to be generated; thus, among so many methods developed for the reuse of this residue that most of the time ends up being discarded, a solution that is being very prominent is the use of malt bagasse in food, this stimulated the creativity of several people who have come to create fiber-rich recipes, and even nutritionists recommending diets with foods made with malt bagasse. The reuse of malt bagasse with food recipes beneficial to human health, is the current noblest cause to avoid inadequate disposal of this residue, but among so many recipes already developed and marketed, new ones are always being made studies to optimize some existing idea or even create a new one.